High sensitivity detection of tumor cells in biological samples using a multivalent aptamer strand displacement strategy. Issue 4 (18th January 2022) - Xu, Jieru; Xiang, Jiahui; Chen, Jialing; Wan, Tao; Deng, Hongli; Li, Dairong
Abstract : The multivalent structure-switching AS1411 aptamer probe based on the displacement strand duplex strategy (designated as "Multi-AS1411 ADSD") was developed for the first time, and is a novel detection strategy for cancer cells. Abstract : Monitoring the cell surface-expressed nucleolin facilitates early cancer diagnosis. Herein, we developed a multivalent aptamer displacement strand duplex strategy on cell membranes using a multi-receptor co-recognition design for improving the sensitivity and specificity of cancer cell recognition with an ultra-low background. The AS1411 aptamer labeled with the FAM fluorophore can be quenched using a partial complementary sequence modified with a BHQ1 tag which is partially hybridized with the AS1411 aptamer to create a receptor-activating aptamer. The multi-AS1411 activable probe based on the strand displacement strategy was constructed using multiple copies of the structure-switching AS1411 aptamer (bearing a short poly-A tail) linked together using the poly-T long chain (as a scaffold) which was synthesized by Terminal Deoxynucleotidyl Transferase (TDT)-mediated extension. We demonstrated the promising efficacy and sensitivity of our method in recognizing tumor cells in both cell mixtures and clinical cytology specimens. Due to its simple and fast operation with excellent cell recognition sensitivity and accuracy, it is expected to achieve the detection of low abundance target cells. Our approach will have broad application in clinical rapid detection and personalized medicine.